Involuntary Resettlement in Brazil : A Review of Policies and Practices - World Bank (Washington, DC, 2013)
The objective of this review of resettlement policy and implementation in Brazil, is to identify ongoing good practices, as well as areas for further improvement. It draws upon an assessment of the Brazilian legal and institutional framework related to land acquisition for projects in the public interest, a rapid evaluation of the resettlement programs in six projects (three projects that received Bank financing and three implemented without Bank support), interviews with experts in this field and with people affected by projects, and a literature review of national and international practices. The key findings and salient recommendations of this study, are summarized, and divided into the categories of identification and mitigation of impacts, institutional responsibility, costing and budgeting, meaningful consultations, grievance redress, monitoring and evaluation. are discussed below